Design and optimization of an opto-acoustic sensor based on porous silicon phoxonic crystals - Forzani, Luisina (2021)
We present the theoretical study of an opto-acoustic microdevice, a phoxonic crystal, made of porous silicon with a specific acoustic response in the range of tens of MHz and optical response in the visible and near-infrared range. We propose to control the opto-acoustic response of this device by spatially modulating the microstructure porosity. Based on this study, a multilayer microcavity is designed to have a strong coupling between the acoustic and optical response. The coupling mechanism is generated by exploiting the structural resonance due to the acoustic waves which produce maximum mechanical strains at the center of the cavity. The associated mechanical deformations of the central cavity change the optical response of the multilayer, allowing the mechanical response to be detected using optical techniques. In a phoxonic crystal, the acoustic and optic central gap frequencies are determined by the multilayer configuration which imposes a fixed relation between both resonant frequencies. This feature establishes a challenge for the microdevice design. To mitigate this problem, two microcavities, one inside the other in a matryoshka-like configuration is here proposed, placing an optical microcavity into the spacer of an acoustic microcavity. Consequently, the localized acoustic field generates a high perturbation of the optical microcavity structure. The optical microcavity is tuned at near-infrared frequencies, while the larger acoustic microcavity resonates at acoustic frequencies of the order of tens of MHz. The microdevice is designed to display a high optical response induced by acoustic deformation. Optical sensitivity to this effect is used to design a multiparametric sensor. Thanks to the porous structure of the device, it is possible to build a transducer sensitive to the presence of analytes in the environment that affect both its mechanical and optical response.